Empowerment of MIM Surodadi 1, Magelang Regency to create disaster resilient schools - Ahwy Oktradiksa; Akhmad Liana Amrul Haq; Helmi Imaduddin (Universitas Muhammadiyah Magelang, 2023)
Madrasah Ibtidaiyah Muhammadiyah (MIM) Surodadi 1 is situated in Surodadi Hamlet, Gondowangi Village, Sawangan District, and falls within the Disaster Risk Area (KRB-2) with a radius of 17 km from the surface of Mount Merapi. However, MIM Surodadi-1 has yet to implement the disaster education policy and adopt SMAB. Activities include Focus Group Discussions (FGDs), simulations, and games. The outcome of these activities involves fortifying the concept of disaster preparedness in schools, employing organizational formats within the school, and enhancing skills to mitigate disaster risks, particularly from a psychological perspective.